ANALISIS STANDAR PENILAIAN PENDIDIKAN - Ahmad Mustopa; Jasim Jasim; Hasan Basri; Ujang Cepi Barlian (Universitas Pakuan, 2021)
Educational Assessment Standards ar ethe criteria regarding mechanisms, the procedures and instruments for assessing student learning outcomes. According to BSNP, the standardized assessment conducted by educators are to include general standards, planning standards, implementation standards, processing and reporting standards for assessment results as well as standards for the use of the assessment results. Each of these standards contained the principles and criteria established by the BSNP. Meanwhile, the assessment of learning outcomes carried out by educational units contains two main standards that must be considered, namely: the standard for determining class promotion and the standard for terminating graduation